Information asymmetry, ownership structure and cost of equity capital: The formation for open innovation - Ade Imam Muslim; Doddy Setiawan (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Our study aims to investigate how information asymmetry and ownership structure affect cost of equity capital. For that purpose, we collected 246 issuers over 4 years for a total of 984 observations. By using panel data processing, we found that the information asymmetry we proxied through Price non-Synchronization and trading volume had an effect on the cost of equity capital. Our results also confirmed both Agency Theory and Pecking Order Theory. Both theories are in line with the conditions of the stock market in Indonesia. In addition, we found that institutional and foreign ownership structures also had an effect on the cost of equity capital. Furthermore, our results also confirmed Interest Alignment Theory and Entrenchment Theory. Our research is expected to contribute to the debate on the existence of information asymmetry and ownership structures in relation to the cost of equity capital. We also hope that it will be a valuable input for investors in considering their investment. Moreover, from the results of this study, investors can also consider foreign ownership or institutional ownership in determining their investment. In addition, stock market regulators in Indonesia can develop approaches to minimize information asymmetry and encourage foreign investors to invest in Indonesia.
Keywords: 650; cost of equity capital; Indonesia; information asymmetric; ownership structure